Hodgkin's Lymphoma, Tuberculoid Leprosy and Amyloidosis in a Single Patient - Botelho, João Bosco L. (2023)
The authors present a clinical association between Hodgkin's Disease, tuberculoid leprosy and amylodosis in anual review of 4652 hystopatological specimens, with incidence: 0,25% of Hodgkin's disease, 1,87% of tuberculoid leprosy, 1,31% of lepromatous leprosy and 0,83% borderline leprosy. The review of medicine literature identified only one publication of two clinical cases of association between Hodgkin's disease and lepromatous leprosy. The immunopatological and clinical aspects of this diseases are separated and discriminated, being notice the relation of immunopatological faces.